Design and Construction of a 200 kV High Voltage Capacitor - Somboonpen, Boonchoo; Poungsri, Piyapat (Journal of Advanced Development in Engineering and Science, 2023)
The purposes of this research are to design and fabricated a high voltage capacitor using insulator of Sulphur hexafluoride (SF6) at pressure gauge of 3 bar in order to obtain the very low dissipation factor at rated voltage of 200 kV, designed and figured with stainless concentric a half of sphere-coaxial cylinder electrode, mounted guard electrode in the insulated PVC tube. All the apparatuses are improved, correctly dimensional specified and constructed in the custom cleanroom. The capacitance of high voltage capacitor is measured and the calibration of high voltage capacitor for constructing a voltage divider as a standard measurement is carried out at High voltage testing department, Transmission system maintenance division, Electricity generating authority of Thailand. The result of the capacitance measurement of capacitor is 50.611 pF when the dissipation factor is 0.001%. The calibration result of voltage divider measurement shows that the average scale factor is 925.99 at uncertainty ±0.61% with a probability of 95% and the Chubb and Fortescue method measurement for peak value of measured voltage shows that the average scale factor is 198.91 at uncertainty ±1.65% with a probability of 95%.